2020
DOI: 10.1108/jsma-11-2019-0196
|View full text |Cite
|
Sign up to set email alerts
|

Market orientation heterogeneity and new joint venture formation announcements: creating value for parent firms

Abstract: PurposeJoint ventures (JVs) are known to create value for their parent firms, in part due to the mutually beneficial sharing of information that occurs at the JV level. Market orientation (MO) is a well-documented strategic orientation that has received little attention in the JV literature, despite considerable research suggesting that MO has a positive effect on performance. This study posits that the MO skills contributed to a new JV by parent firms are likely to play a central role in a shareholder's asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
(134 reference statements)
0
4
0
Order By: Relevance
“…Managers could monitor market reactions to MO in a longitudinal manner, as is done in this study, as well as after corporate communications or announcements (e.g. Jancenelle et al , 2020). By monitoring market reactions to MO, managers may learn which specific level of MO is viewed by shareholders as having the greatest effect on future cashflows.…”
Section: Discussion Implications and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Managers could monitor market reactions to MO in a longitudinal manner, as is done in this study, as well as after corporate communications or announcements (e.g. Jancenelle et al , 2020). By monitoring market reactions to MO, managers may learn which specific level of MO is viewed by shareholders as having the greatest effect on future cashflows.…”
Section: Discussion Implications and Conclusionmentioning
confidence: 99%
“…Indeed, extant research has suggested that profit orientation is only found to be positively related to three out of five performance variables (Kumar et al, 1998). Similarly, long-term focus was not found to improve performance in the joint-venture context (Jancenelle et al, 2020). These prior findings are incongruoussince they do not suggest a positive linear relationship between MO's components and firm performance, contrary to what prior research has usually contended (Kirca et al, 2005) and may be indicative of intricacies not directly addressable by the development simple linear relationship hypotheses (Haans et al, 2016).…”
Section: 6mentioning
confidence: 94%
See 1 more Smart Citation
“…European Journal of Theoretical and Applied Sciences, 1(4), 1031-1055. DOI: 10.59324/ejtas.2023.1(4).98 knowledge is processed to realize firm activities (Li, 2004;Teece, 2007;Jancenelle, 2020;Keen and Wu, 2011;Das and Teng, 2000;Miocevic, 2021;Hoque et al, 2022).…”
Section: Suggested Citationmentioning
confidence: 99%